Aligning the Non-Taxable Income Threshold with Inflation: A Legal Justice Theory Perspective - Daniel Daniel; Gunardi Lie (Fakultas Syariah IAIN Langsa, 2026)
Ideally, the policy on Non-Taxable Income (Penghasilan Tidak Kena Pajak/PTKP) functions as an instrument for minimum economic protection and reflects fiscal justice within the taxation system. However, in reality, the current PTKP threshold has not been adequately aligned with inflationary dynamics and the declining purchasing power of taxpayers, thereby generating substantive injustice, particularly for low- and middle-income groups. This study aims to analyze the urgency of adjusting the PTKP threshold in response to inflation from the perspective of Gustav Radbruch’s theory of legal justice. The research employs a qualitative normative legal method based on library research, utilizing statutory analysis, conceptual approaches, and legal-philosophical inquiry. Primary sources include tax legislation and related regulations, while secondary sources consist of scholarly literature in law and economics. The findings indicate that an inflexible PTKP policy prioritizes legal certainty over justice and utility, resulting in a distortion of the redistributive and welfare-oriented functions of taxation. Consequently, this study argues that periodic and inflation-responsive adjustments to PTKP are essential to achieving substantive legal justice and reinforcing the constitutional mandate of social welfare under the 1945 Constitution of Indonesia.